Активация поверхности композитных материалов на основе полилактида и гидроксиапатита с применением плазменных технологий - Хомутова, Ульяна Викторовна (Перспективы развития фундаментальных наук. Т. 2 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
The effect of low-temperature nitrogen plasma on the physicochemical properties of the surface of composite materials based on polylactic acid/hydroxyapatite at a mass ratio of components (60/40, 70/30, 80/20) has been studied. Elemental composition of the composites surface before and after plasma treatment has been researched by X-ray photoelectron spectroscopy. Phase composition of the composites were studied by Xray phase analysis. The contact angle was measured by the sessile drop technique.